2022
DOI: 10.3390/rs14071618
|View full text |Cite
|
Sign up to set email alerts
|

Differentiate Soybean Response to Off-Target Dicamba Damage Based on UAV Imagery and Machine Learning

Abstract: The wide adoption of dicamba-tolerant (DT) soybean has led to numerous cases of off-target dicamba damage to non-DT soybean and dicot crops. This study aimed to develop a method to differentiate soybean response to dicamba using unmanned-aerial-vehicle-based imagery and machine learning models. Soybean lines were visually classified into three classes of injury, i.e., tolerant, moderate, and susceptible to off-target dicamba. A quadcopter with a built-in RGB camera was used to collect images of field plots at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Our study indicated that RF had the highest classification accuracy in the three regions ( Table 5 , Table 6 and Table 7 ), which is in line with the findings of many classification studies of daytime UAV images [ 12 , 35 , 36 , 37 ]. The RF algorithm integrates multiple decision trees with good high-dimensional data processing capability and can effectively avoid noise interference.…”
Section: Discussionsupporting
confidence: 89%
“…Our study indicated that RF had the highest classification accuracy in the three regions ( Table 5 , Table 6 and Table 7 ), which is in line with the findings of many classification studies of daytime UAV images [ 12 , 35 , 36 , 37 ]. The RF algorithm integrates multiple decision trees with good high-dimensional data processing capability and can effectively avoid noise interference.…”
Section: Discussionsupporting
confidence: 89%
“…Each plot consisted of a single 2.13 m long row spaced 0.76 m apart. The Lee Farm and Rhodes Farm have been exposed to prolonged and homogeneously distributed off-target dicamba damage since 2017, where significant yield losses due to off-target dicamba exposure have been reported between non-DT and DT soybean genotypes (Canella Vieira et al, 2022a;Chen et al, 2022;Canella Vieira et al, 2022b). Off-target dicamba exposure was a result of dicamba volatilization from nearby cropping systems consisting of DT soybean and cotton.…”
Section: Plant Materials and Data Collectionmentioning
confidence: 99%
“…Conventional soybean breeding programs develop new varieties through extensive field trials and phenotypic and genotypic screening to select genotypes with high-yielding potential and desirable economic traits, including off-target dicamba tolerance [ 15 ]. However, the assessment of off-target dicamba damage requires breeders to check hundreds or thousands of genotypes across multiple environments (combination of location, field, and year), which is time-consuming and labor-intensive [ 16 ]. In addition, visual scores may not be accurate due to their subjective nature [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the assessment of off-target dicamba damage requires breeders to check hundreds or thousands of genotypes across multiple environments (combination of location, field, and year), which is time-consuming and labor-intensive [ 16 ]. In addition, visual scores may not be accurate due to their subjective nature [ 16 ]. In recent years, unmanned aerial vehicle (UAV) imaging technology has been extensively used in agriculture for collecting the high spatiotemporal resolution imagery data of crops [ 17 ].…”
Section: Introductionmentioning
confidence: 99%